Inactivation of Salmonella and Escherichia coli in surface agricultural water using a commercial UV processing unit - Usaga Barrientos, Jessie (2022)
Treatment of agricultural water aids in the prevention of foodborne disease outbreaks linked to contaminated fresh produce. UV light is a suitable alternative for treating drinking water but is not always effective for surface irrigation water due to interference caused by turbidity and high microbial loads. The effectiveness of UV treatment for reducing Escherichia coli and Salmonella in surface water used in agriculture was evaluated. Six pond water samples were collected on each of 16 sampling dates over a 3-year period. On each corresponding testing date, three samples were inoculated with Salmonella enterica serovars Hartford, Montevideo, and Gaminara and the other three samples were inoculated with E. coli ATCC 25922, targeting a concentration of 7 log CFU/mL. Inoculated water was UV treated with a commercially available juice processing UV device at a constant UV dose of 14.2 mJ/cm2 and a turbulent flow regime. The effects of date, initial bacterial counts, and water pH and turbidity on log reductions of both microorganisms were determined. Initial bacterial counts and test date significantly predicted microbial reduction (multivariate P < 0.001), but neither pH nor turbidity influenced microbial reductions (P > 0.05). UV treatment reduced both Salmonella and E. coli by a mean of >6 log CFU/mL.